The Characterization physical, mechanical, thermal and morphological properties of Colophony - Kencanawati, Cokorda Istri Putri Kusuma (International Journal of Engineering and Emerging Technology, 2018)
This study aims to determine the characteristics of pine resin as an alternative to resin on composites. Pine resin is pine species studied were merkuzii Jungh. et deVries that grew up in KPH East Bali. Pine resin is very difficult to freeze at room temperature. The pine resin used in the study was heated at 170 0 C for 150 minutes and with a 400 rpm magnetic stirrer speed. Further testing is done to determine the physical, mechanical, thermal and morphological properties of pine resin. Turpentine content in pine resin will decrease with heating treatment. There was a change of color due to heating and the mechanical nature of pine resin very brittle with SEM observation showed no pore in pine resin.